Interrogating pulmonary diffusing capacity in long COVID: insights from DLCO and DLNO testing - Parks, Jordan K.; Johnson, Bruce D.; Shea, Meredith G.; Kim, Chul-Ho; Johnston, Jessica I.; Carlson, Alex; Schwartz, Jesse C.; Wheatley-Guy, Courtney M. (Frontiers in Physiology, 2025)
IntroductionThe lingering respiratory effects of COVID-19, particularly in patients with Long COVID, remain poorly understood, prompting a comprehensive evaluation of lung function in this population.MethodsSimultaneous measurements of diffusion capacity of the lungs for carbon monoxide (DLCO) and nitric oxide (DLNO), chest computed tomography (CT), lung ultrasound and questionnaires were collected in 74 subjects. Participants were categorized into two groups: those that have no lingering symptoms (NS, n = 37) and those still struggling with symptoms after initial infection, the disease known as Long COVID (LC, n = 37).ResultsDLCO and DLNO were significantly lower in the LC group compared to the NS group (LC vs. NS, DLCO: 25.94 ± 7.65 vs. 21.71 ± 6.35 mL/min/mmHg, p = 0.009; DLNO: 148.5 ± 35.6 vs. 126.6 ± 32.2 mL/min/mmHg, p = 0.006). Pulmonary capillary blood volume (Vc) was also significantly lower in the LC group (43.38 ± 13.87, 70.79 ± 17.77, p = 0.003; LC vs. NS, respectively). Alveolar volume (VA) is significantly lower in the LC group (LC vs. NS, 5.06 ± 1.17 vs. 5.95 ± 1.16, p = 0.004). There was no significant difference between groups for surface area of the lungs available for gas exchange by resistance to gas transfer across the alveolar-capillary membrane (DM) between groups (LC vs. NS, 208.63 ± 97.3, 223.0 ± 93.47 mL/min/mmHg, p = 0.54). These findings indicate that Vc is the driving factor of decreased DLCO. CT findings and lung ultrasound showed no differences between the two groups for lung fluid (p = 0.525; p = 0.298).ConclusionThese findings suggest that a lack of volume available for perfusion could be problematic for these patients and as such requires further investigation for clinical management of these patients.